THE INFLUENCE OF KNOWLEDGE SELF-EFFICACY AND PERSONALITY ON KNOWLEDGE SHARING WITH TRUST AS MEDIATOR - Buyung Aulia Safrizal, Helmi; Indriyani, Ratih; Alexandra de J.da Costa, Carla (JURNAL EKBIS, 2024)
Knowledge sharing behavior is influenced by two main factors, namely macro factors originating from the organization, such as organizational culture, leadership, reward and incentive systems, as well as technological aspects such as information systems. The second factor is micro factors originating from the individual, including personality, knowledge, self-efficacy, and trust. Trust is a crucial element in knowledge sharing behavior, as revealed by several studies that the higher the level of trust between management and colleagues, the greater the tendency to share knowledge. The main focus of this research is on individual factors, because they are considered a key element in the success of knowledge management. Knowledge in organizations is created through interactions between employees at various levels, so the individual aspect becomes very important. This research involved 200 permanent employees with more than one year of service, using a non-probability sampling method with accidental sampling technique. This sample size is in accordance with the criteria for structural equation modeling (SEM) with the optimal Maximum Likelihood method for detecting significant differences. The results indicate that organizations need to pay special attention to developing individual factors, especially trust and self-efficacy, to improve knowledge sharing behavior.